Use of a Bundle Checklist Combined With Physician Confirmation Reduces Risk of Nosocomial Complications and Death in Trauma Patients Compared to Documented Checklist Use Alone. Issue 4 (October 2015) - Reiff, Donald A.; Shoultz, Thomas; Griffin, Russell L.; Taylor, Benjamin; Rue, Loring W.
Abstract : Background: Bundle checklists are increasingly utilized in patient care, but data are inconsistent regarding their efficacy in reducing nosocomial complication rates. We examined whether checklist usage was associated with nosocomial complications; when documented, elements were verified by provider bedside rounds. Methods: We performed a retrospective cohort study of trauma patients admitted to our hospital during a three-phase implementation of a quality improvement project. For this analysis, patients were categorized under predocumentation (PD), documentation only (DO), or documentation with provider review (PR) cohort based on temporal designations. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between documentation cohorts and nosocomial complications. Results: No difference was observed in mean hospital stay, intensive care unit (ICU) days, or ventilator days. The DO cohort showed no significant differences in the risk of complications. Among ICU patients, when compared with the PD cohort, the PR cohort demonstrated a decreased risk of all complications OR 0.72 (95% CI 0.55–0.93), pulmonary embolus OR 0.29 (95% CI 0.11–0.73), pneumonia OR 0.66 (95% CI 0.50–0.88), and death OR 0.50 (95% CI 0.31–0.79). Conclusions: Bedside confirmation of bundle checklists during physician extender rounds reduces the risk of pulmonary embolus, pneumonia, and death when compared to chart documentation alone. This study underscores the importance of the team approach to the bundle checklist and it's ability to reduce morbidity and mortality.